A case report of adult juvenile polyposis syndrome with SMAD4 pathogenic variant - Liu, Yutong; Wang, Zeyu; Zhang, Zhongyu; Sun, Yuanyuan; Zhang, Yanyan; Yang, Jiamei (Frontiers in Oncology, 2023)
Abstract：Background: Juvenile polyposis syndrome (JPS) is a rare autosomal dominant disorder that is a type of hamartomatous polyp syndrome, and its incidence rate is approximately 1/100000. The main clinical feature is the presence of multiple juvenile polyps in the gastrointestinal tract, most often in the colorectal tract. We present a case of juvenile polyposis syndrome with massive gastric polyposis. Case presentation: A 50-year-old male was admitted to the hospital due to abdominal distension and poor appetite. Gastroscopy revealed a large number of gastric polyps. Pathological findings revealed gastric juvenile polyps. Genetic testing revealed that he and his brother both carried SMAD4: c.266_269del germline pathogenic variant. The final diagnosis was juvenile polyposis syndrome of the stomach. He once suffered from colon cancer and bladder cancer. His brother died of colon cancer, and his brother suffered from colon polyps. Conclusions: Gastric involvement in juvenile polyposis syndrome is relatively rare. When massive gastric polyposis is found, gene detection should be carried out as soon as possible, so that rapid diagnosis and treatment can be obtained.